INTERNET ADDICTION AND ITS ASSOCIATION WITH ANXIETY IN MEDICAL UNDERGRADUATES–A CROSS-SECTIONAL STUDY - MANDLA, MOUNIKA; GARUGU, BALAJI; VUNNAM, SHASHANKA; GOTTUMUKKULA, VAIDYANATH (International Journal of Current Pharmaceutical Research, 2023)
Objective: To study the prevalence of Internet Addiction among Medical undergraduates and Interns and exploration of its association with anxiety disorders. Methods: It is a cross-sectional survey conducted among 540 undergraduate medical students and 93 Interns at Government Medical College, Ananthapuramu. Young’s Internet Addiction Test and Zung’s self-rated Anxiety scale were applied to measure Internet addiction and Anxiety, respectively. Results: From the results, it was 36.3% of subjects had Internet Addiction, of which 2% had severe Internet Addiction. Anxiety prevalence was about 19.14 %, of which 16.8% had mild to moderate anxiety symptoms and 2.34% had severe anxiety. There was a significant association between Internet Addiction and Anxiety (p<0.0001). There is a negative correlation between the year of study and Internet Addiction (p<0.018). Conclusion: Internet addiction was found among medical students and there was a significant association between Internet addiction and Anxiety among participants.